COMPLICATIONS IN PILONIDAL SINUS AFTER EXCISION AND PRIMARY CLOSURE - Malik Azhar Hussain; Naveed Ashraf Malik (Journal of University Medical & Dental College, 2017)
ABSTRACT Objective: The objective of the present study was to determine the complications of pilonidal sinus after excision and primary closure. Methodology: This was an interventional quasi experimental study conducted at Central Hospital, Arar, Northern borders Region, Saudi Arabia between October 2015 and September 2016. The data was collected from all indoor elective patients who underwent excision and primary closure of chronic pilonidal sinus disease. This data was analyzed with special reference to complication rate and was compared with local and international studies. Results: Fifty nine male patients with pilonidal sinus treated with excision and primary closure were included in the study. Four patients (6.78%) developed wound infection and were treated with appropriate antibiotics; 1 patient (1.69%) developed hematoma, which needed evacuation and healed by itself; 2 patients (3.39%) developed seroma, which was drained by needle and settled on compression dressing; and the recurrence was observed in 2 patients (3.39%) only. In remaining 50 patients (84.74%), course to healing went uneventful and full recovery was achieved as observed in the follow up period. Conclusion: Excision with primary closure of chronic pilonidal sinus disease resulted in full recovery in a good percentage of cases, short hospital stay and earlier discharge. A few patients developed complications and were successfully treated. The recurrence rate was also negligible.